2007
DOI: 10.1007/s00709-006-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the toxicity and distribution of cadmium and lead in plant cells

Abstract: The toxicity of heavy metals (Cd, Zn, and Pb) was assessed by in vivo observations of their effect on cytoplasmic streaming in Allium cepa L. bulb scale epidermal cells. On the basis of our results, the order of toxicity of the studied cations is Zn < Pb << Cd. The difference in toxicity between cadmium and lead was found to be very large. When cytoplasmic streaming was assessed, this difference was threefold. When the total content of cadmium and lead (determined by inductively coupled plasma mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 37 publications
4
64
0
3
Order By: Relevance
“…The results obtained here are consistent with earlier findings [7,11,31,32]. However, Carrier et al [33] reported that approximately 80% of Cd was found predominantly in the soluble fraction, and relatively little Cd was found in the cell wall (11%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results obtained here are consistent with earlier findings [7,11,31,32]. However, Carrier et al [33] reported that approximately 80% of Cd was found predominantly in the soluble fraction, and relatively little Cd was found in the cell wall (11%).…”
Section: Discussionsupporting
confidence: 93%
“…The data from inductively coupled plasma mass spectrometry (ICP-MS) revealed that 56% of total Cd was located in cell walls of Allium cepa epidermal cells exposed to Cd [31]. Similarly, the data from energydispersive x-ray analyses (EDXA) indicated that Cd ions appeared in walls of root cells of A. cepa treated with Cd [42].…”
Section: Discussionmentioning
confidence: 99%
“…Both metals have similar chemical properties: they have similar atomic radius, similar oxidation state in chemical compounds and share similar geochemical properties (Emsley 1991;Kabata-Pendias 2010) and both have been evidenced to interact similarly with different marcomolecules in plant cells (e.g. Przedpelska-Wasowicz et al 2012;PrzedpelskaWasowicz and Wierzbicka 2011;Wierzbicka et al 2007). Taking this into account, similar mechanism could be postulated for both phenomena.…”
Section: Stimulation Of the Onset Of Flowering By Low Zn Concentrationsmentioning
confidence: 93%
“…The lead, that could be bound by certain organic molecules (Piechalak et al 2002;Vadas and Ahner 2009), is sequestered in several plant cell compartments: vacuoles (Małecka et al 2008;Meyers et al 2008), dictyosome vesicles (Malone et al 1974), endoplasmic reticulum vesicles (Wierzbicka et al 2007), or plasmatubules (Wierzbicka 1998).…”
Section: Inducible Mechanismsmentioning
confidence: 99%